Application of GAB Model for Water Desorption Isotherms and Thermodynamic Analysis of Sugar Beet Seeds. Issue 1 (27th August 2015) - de Oliveira, Gabriel Henrique Horta; Corrêa, Paulo Cesar; de Oliveira, Ana Paula Lelis Rodrigues; Reis, Renata Cunha dos; Devilla, Ivano Alessandro
Abstract: The desorption isotherms and thermodynamic properties of sugar beet seeds of cv. "Chata do Egito" variety was determined at 10, 20, 30, 40 and 50C over a range of water activities ( A w ) from 0.11 to 0.96. Equilibrium moisture content data were correlated by the Guggenheim–Anderson–de Boer model, which presented good fit to the data, according to statistical procedures. Equilibrium moisture content ranged from 1.50 to 20.0% d.b. (dry basis). Desorption isotherms of sugar beet seeds exhibited type II sigmoid shape. Thermodynamic properties were determined related to desorption process. Differential enthalpy values varied between 3, 614.51 and 4, 093.90 kJ/kg. Differential entropy and Gibbs free energy presented values between 3.67–4.08 kJ/kg.K and 0.75–508.11 kJ/kg, respectively. The enthalpy–entropy compensation theory is valid for the moisture desorption phenomena of sugar beet seeds, being enthalpy controlled. Practical Applications: Almost 100% of the Brazilian sugar beet seeds are imported throughout the world and its commerce between different countries. Higher distances lead to physical, chemical and microbiological changes in sugar beet seeds. This trend could cause the deterioration of food products. Information on the sorption characteristics of sugar beet seeds could not be found in the literature, regardless of this culture importance. Sorption isotherms data are key information to predict optimum storage and trading conditions to ensure quality of sugar beet seeds for crop production. Finally, the lack of quality may affect employees, entrepreneurs and other professionals who work with sugar beet. This paper presents the desorption isotherms and thermodynamic properties of "Chata do Egito" sugar beet seed variety.